No Safe Place : Toxic Waste, Leukemia, and Community Action. - Brown, Phil (University of California Press, 1997)
A focus on a community's struggle for justice in the wake of the environmental contamination by local corporations. Readers will learn about how the residents of Woburn, Massachusetts discovered a childhood leukaemia cluster and eventually sued two corporate giants.